Interpretasi Psikoterapi Dalam Mujahadah Malam - Fikri Hailal; Latipah, Eva; Nuroh, Siti (Jurnal Studi Islam dan Sosial, 2024)
This article is based on the article "Esoteric Study of Mujahadah Nights: A Review of Ulric Neisser's Cognitive Psychology", explaining night mujahadah activities at the Raudlotul Huda Islamic boarding school, Margoyoso, Jepara. Mujahadah means being serious, using all your energy and thoughts to achieve your goal. The article conveys the night mujahadah procession as part of the subjective, esoteric aspect. The purpose of this writing is to interpret the esoteric aspects of night mujahadah from a psychotherapy perspective. The cornerstone of the question as a trigger for discussion is how is the interpretation of psychotherapy in night mujahadah and how is the actualization of psychotherapy practicing night mujahadah wadhifah? The approach used is an interpretive approach, Paul Ricoeur. By using qualitative content analysis methods. The results of this research are 1) the practice of night mujahadah psychotherapy is carried out such as morning prayers and continued reading awradul mujahadah accompanied by a surrendered heart (wa antalqahu bil qabul) and appreciation, and 2) the actualization of night mujahadah psychotherapy is aimed at solving problems. This actualization is considered capable of being a support system for practitioners who experience a crisis or psychological trauma. So it becomes an antidote to psychosomatic disorders and indications of psychopathological disorders.